Teaching physics in echnical university using electronic environment moodle; 11th International Technology, Education and Development Conference (INTED2017), 6-8 March, 2017, Valencia, Spain - Kravchenko N. S. Nadezhda Stepanovna; Lisichko E. V. Elena Vladimirovna; Postnikova E. I. Ekaterina Ivanovna; Daneykina (Daneikina) N. V. Natalia Viktorovna (2017, 2017)
Title screen